Printemps arabe : de l’événement à la formule discursive - Nadjia Nehari-Roubai (OpenEdition, 2018)
The expression of "Arab Spring" designating the movements that broke out in 2011 in Tunisia and then in other Arab countries, has occupied a considerable place in political, media and public speeches. From its status as a neologism, the expression accesses a new function in the discourse : that of formula. Inspired by the works of Alice Krieg-Planque on formula in discourse analysis, the perspective proposed in this article is to question the notion of "Arab Spring" and follow the change in its discursive formula related to the event and its interpretation through the discursive space in which it participates.